Uji Efektivitas Ekstrak Etanol Serai (Cymbopogon Citratus) terhadap Kadar Trigliserida pada Tikus Putih dengan Obesitas - Sherliana, Sherliana; Hidayati, Prema Hapsari; Irmayanti, Irmayanti; Kartika, Irna Diyana; Nurmadilla, Nesyana (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT This study This study aims to compare triglyceride levels in white rats that only given a high-fat diet (negative control group), comparing triglyceride levels in white rats with the administration of triglyceride levels in white rats given lemongrass ethanol extract (Cymbopogon Citratus) with white rats given simvastatin with a high-fat diet (negative control group). white rats given simvastatin with a high-fat diet (positive control group), comparing triglyceride levels in white rats with positive control group), comparing triglyceride levels in white rats before and after the administration of lemongrass ethanol extract at a dose of 150mg/dl with a high-fat diet, comparing triglyceride levels in white rats before and after the administration of the fat diet, comparing triglyceride levels in white rats before and after the administration of lemongrass ethanol extract at a dose of 200mg/dl with a high-fat diet, comparing triglyceride levels in white rats before and after administration of lemongrass ethanol extract with a dose of 250mg/dl with a high-fat diet, comparing triglyceride levels in white rats after the intervention for 14 days in all groups, and to compare the effectiveness of triglyceride levels in all groups of obese white rats. Research conducted conducted was an experimental study with a pre and post test control group design using mice. post test control group design using white rats (Rattus Novergicus) who are obese as experimental animals to determine the effects of administration of lemongrass ethanol extract (Cymbopogon Cytratus) to reduce triglyceride levels of white rats. triglyceride levels of obese white rats. The results showed that rats that were not given lemongrass ethanol extract or simvastatin showed higher triglyceride levels. triglyceride levels, which confirms that lemongrass ethanol extract may serve as an alternative in reducing triglyceride levels in obesity. Lemongrass ethanol extract showed a reduction in triglyceride levels that was almost equivalent to simvastatin. almost equivalent to simvastatin, although simvastatin was slightly more effective in reducing triglycerides in the control group. Administration of lemongrass ethanol extract lemongrass at a dose of 150mg significantly reduced triglyceride levels in obese white rats. Administration of lemongrass ethanol extract at a dose of 200mg significantly reduced triglyceride levels in obese white rats. significantly reduced triglyceride levels in obese white rats. Giving lemongrass ethanol extract at a dose of 250mg did not provide a significant decrease in triglyceride levels. significant decrease in triglyceride levels in obese white rats. There is a significant difference in triglyceride levels in obese white rats after the  intervened 14 days in all groups. The decrease in triglyceride levels was more effective in the positive control group with simvastatin control group with simvastatin, however, the group with the 150mg/dl and 200mg/dl extract interventions also experienced a significant decrease in triglyceride levels. in obese white rats. Keywords: Cymbopogon Citratus, Obesity, Triglyceride, Ethanol Extract, White Rat  ABSTRAK Penelitian ini bertujuan untuk membandingkan kadar trigliserida pada tikus putih yang hanya diberikan diet tinggi lemak (kelompok kontrol negatif), membandingkan kadar trigliserida pada tikus putih dengan pemberian ekstrak etanol  serai (Cymbopogon Citratus) dengan tikus putih yang diberikan obat simvastatin dengan diet tinggi lemak (kelompok kontrol positif), membandingkan kadar trigliserida pada tikus putih sebelum dan setelah pemberian ekstrak etanol serai dengan dosis 150mg/dl dengan diet tinggi lemak, membandingkan kadar trigliserida pada tikus putih sebelum dan setelah pemberian ekstrak etanol serai dengan dosis 200mg/dl dengan diet tinggi lemak, membandingkan kadar trigliserida pada tikus putih sebelum dan setelah pemberian ekstrak etanol serai dengan dosis 250mg/dl dengan diet tinggi lemak, membandingkan kadar trigliserida pada tikus putih seteleh intervensi selama 14 hari pada semua kelompok, serta untuk membandingkan efektivitas terhadap penurunan kadar trigliserida pada semua kelompok tikus putih dengan obesitas. Penelitian yang dilakukan adalah penelitian eksperimental dengan rancangan penelitian pre and post test control group design dengan menggunakan tikus putih (Rattus Novergicus) yang obesitas sebagai hewan coba untuk mengetahui efek dari pemberian ekstrak etanol serai (Cymbopogon Cytratus) terhadap penurunan kadar trigliserida dari tikus putih yang obesitas. Hasil penelitian menunjukkan bahwa tikus yang tidak diberi ekstrak etanol serai atau simvastatin menunjukkan kadar trigliserida yang lebih tinggi, yang mengonfirmasi bahwa ekstrak etanol serai dapat berfungsi sebagai alternatif dalam mengurangi kadar trigliserida pada obesitas. Ekstrak etanol serai menunjukkan penurunan kadar trigliserida yang hampir setara dengan simvastatin, meskipun simvastatin sedikit lebih efektif dalam menurunkan trigliserida pada kelompok kontrol. Pemberian ekstrak etanol serai dengan dosis 150mg secara signifikan menurunkan kadar trigliserida pada tikus putih obesitas. Pemberian ekstrak etanol serai dengan dosis 200mg secara signifikan menurunkan kadar trigliserida pada tikus putih obesitas. Pemberian ekstrak etanol serai dengan dosis 250mg tidak memberikan penurunan secara signifikan pada  kadar trigliserida pada tikus putih obesitas. Terdapat adanya perbedaan yang signifikan kadar trigliserida pada tikus putih obesitas setelah  diintervensi 14 hari  pada semua kelompok. Penurunan kadar trigliserida lebih efektif pada kelompok kontrol positif yang diintervensi simvastatin,meskipun demikian kelompok dengan intervensi ekstrak 150mg/dl dan 200mg/dl juga mengalami penurunan yang signifikan pada tikus putih obesitas. Kata Kunci:  Cymbopogon Citratus, Obesitas, Trigliserida, Ekstrak Etanol, Tikus Putih